The broad positive health perspective on health as common ground for tackling current and future interdisciplinary health challenges - Dierx, John A. J.; De Bot, Cindy M. A. (Frontiers in Public Health, 2025)
In the past decades, many developments on economy, demography and technology amongst others have directly or indirectly influenced population health both in a positive and negative way. Consequently, the population is aging with accompanying demand for care while the workforce in health care and wellbeing is decreasing. A so-called infarction in health care and wellbeing is pending. This calls for a shift in perspective on health as care can be prevented by healthy lifestyle and resilience and self-reliance could be increased. Positive Health (PH) introduces such an innovative shift in healthcare, prioritizing resilience, adaptability, and overall well-being over traditional disease-focused models. This Perspective article explores the possible definitions of health and the development of PH, its pros and cons, application of the concept in the Netherlands and some examples worldwide and finally and discusses the global opportunities and challenges it poses. The article highlights future pathways toward a patient-centred and sustainable healthcare system, and it is suggested that the PH perspective could be instrumental in this emphasizing intersectoral collaboration, ethical considerations, and integration into healthcare frameworks.